Top Five Ranking of Sharia Financial Acades with the Potential of Fraud (Case Study of Three Sharia Commercial Banks) In North Sumatera - M. Yasir Nasution; Andri Soemitra; Wilchan Robain (Budapest International Research and Critics University, 2021)
The purpose of this study was to find the top five rankings of sharia finance contracts with the potential for fraud (case study of three sharia commercial banks) in North Sumatra. This research uses a combination of quantitative and qualitative research methods, data analysis with Analytical Networking Process (ANP) techniques through Super Decision Software, conducting open and in-depth interviews with 9 respondents, Focus Group Discussion (FGD) with practitioners and sharia finance experts. In this case, it was found that the top five rankings of sharia financial contracts have the potential for fraud (a case study of three sharia commercial banks) in North Sumatra, namely Ijarah 23.34%, murabahah 14.86%, kafalah or kafalah bil ujrah 8.71%, musyarakah 8.22% and mudharabah 6.28%.